Option Values in Sequential Markets - N.-H. M. von der Fehr; C. Riis (University of Oslo, Department of Economics, 1998)
We consider competitive behaviour in sequential markets when current success or failure may affect the probability of future market opportunities. The analysis is conducted in a set up which may be interpreted as two private-value, sealed-bid, second-price sequential auctions. We demonstrate that whether agents price higher or lower than in the corresponding static context depends on the relative magnitudes of the 'winner's option value' and the 'loser's option value' of participating in the later market.
Keywords: D43; D44; D92; 330; auctions